Applying AutoCAD 2006 - T. Wohlers Terry (MC Graw Hill, 2006)
Applying AutoCAD 2006 is a comprehensive, basic CAD textbook providing step-by-step instruction for new users of the AutoCAD computer-aided drafting and design, version 2006. Applying AutoCAD 2006 is a major revision to accommodate the changes in AutoCAD 2006 software. New chapters on dynamic blocks and tables bring Applying AutoCAD 2006 into the 21st century.